Vernacular Nationalism and Sufi Hermeneutics in Shodiq Hamzah’s Al-Bayān fī Ma‘rifat Ma‘ān Al-Qur’ān - Miftahul Jannah; M. Badruz Zaman; Shilvia Shauqil Firdaus (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2025)
This article examines the nexus between Sufism and nationalism through the hermeneutical framework of Al-Bayān fī Ma‘rifat Ma‘ān Al-Qur’ān written by Shodiq Hamzah Usman, a pesantren-based scholar from Central Java. The study analyzes how Qur’anic interpretation in Al-Bayān integrates classical exegetical traditions with local vernacular strategies to articulate social-ethical values within the Indonesian context. The research employs a hermeneutical approach by focusing on Shodiq’s incorporation of Javanese vernacular (Latinized Pegon) and the inclusion of rubrics such as faḍīlat al-sūrah, asbāb al-nuzūl, and qiṣṣah. The analysis demonstrates that values of iḥsān (moral excellence), raḥmah (compassion), and tasāmuḥ (tolerance) are transformed from personal-spiritual ethics into socio-political virtues that underpin inclusive civic leadership, solidarity, and structural justice. Notably, Shodiq links the Qur’anic notion of raḥmah to Indonesia’s nationalist struggle, including Soekarno’s liberation of West Irian, which illustrates a unique vernacular nationalism rooted in Sufi ethics. While Al-Bayān successfully vernacularizes Qur’anic values for pesantren audiences, its normative-descriptive style limits engagement with structural issues such as systemic injustice or global discourses on human rights. This study contributes to broader debates on Indonesian Islam, civil Islam, and the role of Sufism in shaping public virtue and national identity.